Evaluation of the gene-specific dye bias in cDNA microarray experiments - Martin-Magniette, Marie-Laure; Aubert, Julie; Cabannes, Eric; Daudin, Jean-Jacques (Bioinformatics, 2005)
Motivation: In cDNA microarray experiments all samples are labeled with either Cy3 or Cy5. Systematic and gene-specific dye bias effects have been observed in dual-color experiments. In contrast to systematic effects which can be corrected by a normalization method, the gene-specific dye bias is not completely suppressed and may alter the conclusions about the differentially expressed genes. Methods: The gene-specific dye bias is taken into account using an analysis of variance model. We propose an index, named label bias index, to measure the gene-specific dye bias. It requires at least two self–self hybridization cDNA microarrays. Results: After lowess normalization we have found that the gene-specific dye bias is the major source of experimental variability between replicates. The ratio (R/G) may exceed 2. As a consequence false positive genes may be found in direct comparison without dye-swap. The stability of this artifact and its consequences on gene variance and on direct or indirect comparisons are addressed. Availability: http://www.inapg.inra.fr/ens_rech/mathinfo/recherche/mathematique Contact: mlmartin@inapg.fr